The ability of streptomycin-loaded chitosan-coated magnetic nanocomposites to possess antimicrobial and antituberculosis activities - El Zowalaty, Mohamed Ezzat; Hussein-Al-Ali, Samer Hassan; Husseiny, Mohamed I.; Geilich, Benjamin M.; Webster, Thomas Jay; Hussein, Mohd Zobir (Dove Medical Press, 2015)
Magnetic nanoparticles (MNPs) were synthesized by the coprecipitation of Fe2+ and Fe3+ iron salts in alkali media. MNPs were coated by chitosan (CS) to produce CS-MNPs. Streptomycin (Strep) was loaded onto the surface of CS-MNPs to form a Strep-CS-MNP nanocomposite. MNPs, CS-MNPs, and the nanocomposites were subsequently characterized using X-ray diffraction and were evaluated for their antibacterial activity. The antimicrobial activity of the as-synthesized nanoparticles was evaluated using different Gram-positive and Gram-negative bacteria, as well as Mycobacterium tuberculosis. For the first time, it was found that the nanoparticles showed antimicrobial activities against the tested microorganisms (albeit with a more pronounced effect against Gram-negative than Gram-positive bacteria), and thus, should be further studied as a novel nano-antibiotic for numerous antimicrobial and antituberculosis applications. Moreover, since these nanoparticle bacteria fighters are magnetic, one can easily envision magnetic field direction of these nanoparticles to fight unwanted microorganism presence on demand. Due to the ability of magnetic nanoparticles to increase the sensitivity of imaging modalities (such as magnetic resonance imaging), these novel nanoparticles can also be used to diagnose the presence of such microorganisms. In summary, although requiring further investigation, this study introduces for the first time a new type of magnetic nanoparticle with microorganism theranostic properties as a potential tool to both diagnose and treat diverse microbial and tuberculosis infections.